Some Common Fixed Point Theorems in Generalized Metric Spaces - Manoj Kumar; Pankaj Kumar; Sanjay Kumar (Journal of Mathematics)
First we prove common fixed point theorems for weakly compatible maps which generalize the results of Chen (2012). Secondly, we prove common fixed point theorems using property E.A. along with weakly compatible maps. At the end, we prove common fixed point theorems using common limit range property (CLR property) along with weakly compatible maps.